2021
DOI: 10.1371/journal.pone.0251702
|View full text |Cite
|
Sign up to set email alerts
|

Rabies post-exposure healthcare-seeking behaviors and perceptions: Results from a knowledge, attitudes, and practices survey, Uganda, 2013

Abstract: Background Rabies is a viral disease of animals and people causing fatal encephalomyelitis if left untreated. Although effective pre- and post-exposure vaccines exist, they are not widely available in many endemic countries within Africa. Since many individuals in these countries remain at risk of infection, post-exposure healthcare-seeking behaviors are crucial in preventing infection and warrant examination. Methodology A rabies knowledge, attitudes, and practices survey was conducted at 24 geographically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…The majority of respondents (97%) declared they would seek medical advice, 92% visited a hospital after a bite incident, and 88% completed the full PEP course. This compliance is quite exceptional and in contrast to e.g., results from Uganda [37] where only 56% of the interviewees indicated that dog-bite victims should visit a hospital and only 3 percent received PEP. While traditional therapies may be an issue in other socio-cultural settings [37,[85][86][87], in this study only six respondents (1.5%) declared that they sought traditional treatment, despite the fact that 8% (298/3726) mentioned that they were aware of various traditional methods of treatment relating to dog bites in humans but also regarding the treatment of dog bite wound in dogs (S8 Table ).…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 77%
See 1 more Smart Citation
“…The majority of respondents (97%) declared they would seek medical advice, 92% visited a hospital after a bite incident, and 88% completed the full PEP course. This compliance is quite exceptional and in contrast to e.g., results from Uganda [37] where only 56% of the interviewees indicated that dog-bite victims should visit a hospital and only 3 percent received PEP. While traditional therapies may be an issue in other socio-cultural settings [37,[85][86][87], in this study only six respondents (1.5%) declared that they sought traditional treatment, despite the fact that 8% (298/3726) mentioned that they were aware of various traditional methods of treatment relating to dog bites in humans but also regarding the treatment of dog bite wound in dogs (S8 Table ).…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 77%
“…Objectives may include provision of baseline data for planning, implementing and evaluating national control programs, identifying knowledge gaps, cultural beliefs, and behavior patterns and barriers to infectious disease control, and designing public health or disease awareness campaigns [ 18 ]. Numerous KAP surveys on rabies have been published from African countries with widely varying targets, e.g., Benin [ 19 ], Burkina Faso [ 20 ], Cameroon [ 21 ], Chad [ 22 ], Côte d’Ivoire [ 23 ], Democratic Republic of the Congo [ 24 ], Ethiopia [ 25 28 ] Ghana [ 29 ], Mali [ 30 ], Morocco [ 31 ], Nigeria [ 32 ], Rwanda [ 33 ], Senegal [ 34 ] Tanzania [ 18 , 35 ], Uganda [ 36 , 37 ], and Zimbabwe [ 38 ]. In Namibia, rabies tailored KAP surveys have been conducted only on a small scale, e.g., individual towns or constituencies in the NCAs [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Survey sites were selected by Ministry of Health officials to coincide with city corporations and peri-urban upazillas (sub-districts) randomly where canine vaccination campaigns were being conducted. A structured questionnaire with Bengali translation was modified from questionnaires previously conducted in other countries to collect data through a face-to-face interview with participants in the selected sites [15,16]. Knowledge, attitudes, and practices (KAP) survey questions collected information pertaining to (i) demographics, (ii) dog bite rates, (iii) attitudes about dog bites and dog ownership, (iv) willingness to pay for human rabies vaccination, (v) healthcare access knowledge, (vi) rabies disease and vaccination knowledge, (vii) dog ownership practices, (viii) biting dog health status, and (ix) campaign awareness and barriers to rabies vaccinations for dogs (S1 Text).…”
Section: Survey and Study Populationmentioning
confidence: 99%
“…results from Uganda [37] where only 56% of the interviewees indicated that dog-bite victims should visit a hospital and only 3 percent received PEP. While traditional therapies may be an issue in other socio-cultural settings [37,8486], in this study only six respondents (1.5%) declared that they sought traditional treatment, despite the fact that 8% (298/3726) mentioned that they were aware of various traditional methods of treatment relating to dog bites in humans but also regarding the treatment of dog bite wound in dogs (S7 Table).…”
Section: Discussionmentioning
confidence: 99%